A multi‐targeted treatment approach to cancer cachexia: Auckland's Cancer Cachexia evaluating Resistance Training (ACCeRT) trial. Issue 1 (9th February 2020) - Rogers, Elaine S.; Sasidharan, Rita; Sequeira, Graeme M.; Wood, Matthew R.; Bird, Stephen P.; Keogh, Justin W.L.; Arroll, Bruce; Stewart, Joanna; MacLeod, Roderick D.
Abstract: Background: Cancer cachexia is a condition often seen at diagnosis, throughout anti‐cancer treatments and in end‐stage non‐small‐cell lung cancer patients. Methods and results: Participants with late‐stage non‐small‐cell lung cancer and cachexia (defined as ≥5% weight loss within 12 months) were randomly assigned 1:2 to 2.09 g of eicosapentaenoic acid (EPA) and 300 mg of cyclo‐oxygenase‐2 inhibitor celecoxib orally once daily vs. same dosing of EPA, celecoxib, plus two sessions per week of progressive resistance training and 20 g of oral essential amino acids high in leucine in a split dose over 3 days, after each session. Primary endpoint was the acceptability of the earlier multi‐targeted approach. Main secondary endpoints included change in body weight and fat‐free mass, by bioelectric impedance analysis and total quadriceps muscle volume by magnetic resonance imaging over 20 weeks. Sixty‐nine patients were screened resulting in 20 patients being enrolled. Acceptability scored high, with 4.5/5 (Arm A) and 5/5 (Arm B) for EPA and 5/5 for celecoxib within both arms and 4.8/5 for progressive resistance training sessions and 4.5/5 for essential amino acids within Arm B, all at Week 20. Results showed a net gain in bioelectric impedance analysis fat‐free mass of +1.3 kg, n = 2 (Arm A), compared with +0.7 kg, n = 7 (Arm B) at Week 12, and —1.5 kg, n = 2 (Arm A), compared with —1.7 kg, n = 4 (Arm B) at Week 20. Trends in efficacy in terms of improvement and/or stability in cachexia markers were seen within magnetic resonance imaging muscle volume, albumin, and C‐reactive protein levels within both arms. There were no exercise‐related adverse events, with one possible related adverse event of asymptomatic atrial fibrillation in one participant within Arm A. Conclusions: Non‐small‐cell lung cancer cachectic patients are willing to be enrolled onto a multi‐targeted treatment regimen and may benefit from cachexia symptom management even during the late/refractory stage.